Modelling thresholds and volatility in US ecological patents - Chan, Felix; Marinova, Dora; Mcaleer, M. (Elsevier SCI Ltd, 2005)
Ecological patents have been increasing steadily over time. This paper analyses trends and volatility in ecological patents in the USA from 1975 to 1997. Germany contributed more than 10% of the total US ecological patents, and is by far the strongest foreign performer. This paper estimates a set of novel regime-switching models to investigate the time-varying nature of the conditional mean, as well as the conditional variance of the patent ratio, namely the ratio of US ecological patents to total US patents, using monthly data from January 1975 to December 1997. The regime-switching LSTAR-GARCH model is found to be optimal for modelling the ecological patent ratio.